2017
DOI: 10.1016/j.juro.2016.07.072
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Active Surveillance after Initial Surveillance Prostate Biopsy

Abstract: Patients on active surveillance with stable disease at the time of initial surveillance prostate biopsy may be appropriate candidates for less intensive surveillance prostate biopsy schedules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…15, 16 Algorithm 8 (no treatment and at least one prostate biopsy after diagnosis) was selected because it has the highest specificity. The repeat biopsy was required to be at least one month after, but within 12 months of, prostate cancer diagnosis to capture a true “confirmatory biopsy.” 17 Finally, Algorithm 6 (no treatment, age less than 75 years, and comorbidity score less than 3) was selected because it has the second highest specificity while maintaining considerably more sensitivity than Algorithm 8.…”
Section: Methodsmentioning
confidence: 99%
“…15, 16 Algorithm 8 (no treatment and at least one prostate biopsy after diagnosis) was selected because it has the highest specificity. The repeat biopsy was required to be at least one month after, but within 12 months of, prostate cancer diagnosis to capture a true “confirmatory biopsy.” 17 Finally, Algorithm 6 (no treatment, age less than 75 years, and comorbidity score less than 3) was selected because it has the second highest specificity while maintaining considerably more sensitivity than Algorithm 8.…”
Section: Methodsmentioning
confidence: 99%
“…Nine prospective studies of AS have included about 10 000 men [38] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] . The largest most mature studies are summarized in Table 3 .…”
Section: Expected Outcomesmentioning
confidence: 99%
“…The results of the Protect trial have recently been reported [52] . This was a randomized trial comparing active monitoring, radical prostatectomy, and external-beam radiotherapy [48] . The primary end point was prostate cancer mortality at 10 years.…”
Section: Expected Outcomesmentioning
confidence: 99%
“…However the risk of misclassification still exists. [13] It has been believed that low risk PCa does not need immediate intervention because of its low-risk potential for metastases. However, some men may initially appear to have low-risk disease but in fact they have disease reclassified to higher risk.…”
Section: Introductionmentioning
confidence: 99%